Integration of Biological Control and Host Plant Resistance Breeding: A Scientific and Literature Review - Thomas, Matthew; Waage, Jeff (Technical Centre for Agricultural and Rural Cooperation, 1996)
The subjects covered include IPM, biological control and host-plant resistance...